A Single Phase GaN GITs-Based Bidirectional Multilevel Inverter for High Voltage Grid Tied Photovoltaic Power System. Issue 8 (9th May 2023) - Naveed, Muhammad Mohsin; Castellazzi, Alberto
Abstract—: In this article, a performance comparison has been conducted between Si MOSFETs, SiC MOSFETs, and Gallium nitride (GaN) GITs in single phase BSNPC inverter. The PSpice study shows that the All GaN GITs BSNPC inverter has the highest efficiency of 98.97% compared to all other power devices used in the simulations. Due to a low dead time of 50 ns, the THD in output voltage for the All GaN GITs BSNPC inverter has decreased by 10% compared to the All Si MOSFETs BSNPC inverter and by 0.5% compared to the All SiC MOSFETs BSNPC inverter. The operation of GaN GITs at 200 kHz resulted in a 63% reduction in output filter size compared to the operation at 10 kHz. The Gate Drive circuit for GaN GITs and its complete design is presented. The All GaN GITs BSNPC inverter laboratory prototype study shows that at 16 kHz, 700 W the maximum efficiency of 99.4% is achieved whereas at 64 kHz, 350 W the lowest efficiency of 98.7% is achieved. The performance of the two GaN GITs connected in series to make a single series bidirectional switch is very reliable and robust. When the switching frequency is increased from 16 kHz to 64 kHz at 700 W output power, the reduction in the output filter size is 35%. The reduction in THD in the output voltage is 8.3% for the GaN GITs when operated at 150 ns dead time compared to 1 μs dead time.